ETUDE PHYTOCHIMIQUE ET POUVOIR ANTIOXYDANT DE L’ECORCE D’ORANGE ET CITRON - Hamidi, Fatima; Limam, Fadila (My University, 2018)
Citrus as other fruit and vegetables are an important source of various antioxydants (polyphénols, caritenoids, ascorbic…etc) these compounds have beneficial effects on human health because they have many biological activities such as antioxidant activity, anti-inflammatory, antibacterial ...... ect, which protects and inhibits the harmful effects of free radicals on the human body. Ethanolic extracts of citrus limon bark and citrus sinensis were tested for their antioxidant activities. The phenolic compounds (total poly phenols and flavonoids) extracted with the extraction solvent (ethanol) showed variations according to the extract and variety, in vitro antioxidant potency assessment revealed antioxidant abilities in all extracts. For this, several extraction methods have been used The first part of this study concerns the extraction and quantification of total phenols, flavonoids by the folin - ciocalteu reagent, and aluminum trichloride. The second part is the study of the antioxidant activity of plant extracts using techniques such as: Trapping of the radical DPPH, anti-radical power of FRAP iron. The results obtained were very significant and the correlation between the antioxidant activity and the content of total phenol compounds was also investigated. The results we achieved showed that:  The total polyphenol content in the ethanolic extracts shows different results which are 83.5; 91.33mg GAE / g ES, corresponding to the following extracts respectively: orange peel, lemon peel.  we observed that lemon peel has more flavonoid amount of 246,25mg / ml, followed by orange peel of 81,375 mg / ml.  the increase in iron reduction is proportional with the increase in the concentration of ascorbic acid and the two extracts of citrus peel.  All our extracts have significantly lower antioxidant activity than the reference (ascorbic acid), for the latter the reduction is almost total from a concentration of 0.063 mg / ml.
Keywords: Citrus; polyphénols; activité antioxydante; DPPH; FRAP; polyphenols; antioxidant activity